The Nursing Interventions for Smoking Cessation in a Hospital Setting - Tahlil, Teuku (Asosiasi Institusi Pendidikan Ners Indonesia (AIPNI), 2023)
The Nursing Interventions for Smoking Cessation in a Hospital Setting